Scleral Fixation of Akreos AO60 Intraocular Lens Using Gore-Tex Suture: An Eye on Visual Outcomes and Postoperative Complications. (20th December 2021) - Leuzinger-Dias, Mariana; Lima-Fontes, Mário; Rodrigues, Rita; Oliveira-Ferreira, Cláudia; Madeira, Carolina; Falcão-Reis, Fernando; Fernandes, Vítor; Rocha-Sousa, Amândio; Falcão, Manuel
Abstract : Purpose . "In-the-bag" placement of an IOL is the Holy Grail for any cataract surgeon. However, in the absence of capsular integrity, alternative surgical options to place the IOL must be sought. We aim to report the clinical outcomes and safety profile of scleral-fixated Akreos AO60 intraocular lens implantation using Gore-Tex suture, combined with pars plana vitrectomy. Methods . This is a single-center, retrospective case series descriptive study. Electronic clinical records of all patients subjected to scleral fixation of a Bausch and Lomb Akreos AO60 IOL combined with pars plana vitrectomy, between April 1, 2017, and August 1, 2021, were reviewed. Data concerning age, sex, laterality, past ophthalmological history, pre- and postoperative best-available visual acuity, surgical indication, and intra- and postoperative complications were collected. Measured outcomes were the differences in best-available visual acuity and frequency of postoperative complications. Results . A total of 37 eyes (20 right eyes and 17 left eyes) from 36 patients (16 females and 20 males) were included in the statistical analysis. The mean age at time of surgery was 72.0 ± 12.4 years. The mean follow-up period was 548.9 days (range 39–1564 days). Globally, the mean best-available logMAR visual acuity improved from 1.61 preoperatively (0.025 decimal equivalent) to 0.57 postoperatively (0.3 decimal equivalent), this difference being statistically significant (P < 0.001 ). Indications for surgery included aphakia due to complicated cataract surgery (24.3%; n  = 9); subluxated IOL due to closed trauma (21.6%; n  = 8); PEX-related subluxated IOL (16.2%; n  = 6); non-traumatic, non-PEX-related subluxated IOL (18.9%; n  = 7); subluxated crystalline lens due to closed trauma (8.1%; n  = 3); aphakia due to open-globe injury (5.4%; n  = 2); silicone-induced IOL opacification (2.7%; n  = 1); and aphakia post-endophthalmitis (2.7%; n  = 1). Postoperative complications included transient ocular hypertension (27.0%; n  = 10), transient corneal edema (18.9%; n  = 7), cystoid macular edema (18.9%, n  = 7), self-limited hypotension (5.4%, n  = 2), self-limited vitreous hemorrhage (2.7%, n  = 1), central retinal vein occlusion (2.7%, n  = 1), late retinal detachment (2.7%, n  = 1), and Akreos IOL opacification (2.7%, n  = 1). No suture-related complications were observed. Conclusion . There was a statistically significant improvement in visual acuity after scleral fixation of Akreos AO60 intraocular lens using Gore-Tex suture, with no suture-related problems recorded. This procedure seems to be a valuable alternative for posterior chamber IOL placement when secondary IOL implantation is required.